Molecular prevalence of feline morbillivirus in shelter cats - Omar, Nurul Husna (2016)
Feline morbillivirus (FmoPV) is an enveloped virus with non-segmented negative strands RNA genomes belongs to the genus of Morbillivirus under the family of Paramyxoviridae. Previously, there were no known morbillivirus infecton in domestic cats. However, a study was done in Hong Kong, in which they discovered a novel virus that was later named as FmoPV. This was followed by discovery and isolation of FmoPV in Japan and Europe. Recently, a screening study of FmoPV was conducted in Malaysia and the prevalence rate was found to be 48.6%. In the present study, urine samples were taken from 46 cats, randomly from three participating shelter organization. The collecting samples were then subjected to nested polymerase chain reaction (PCR) assay amplifying the L gene of FmoPV for final products of 401 bp. Out of 46 samples collected, 19 samples were tested positive for the virus FmoPV. The prevalence rate of FmoPV in shelter cats in Malaysia is 41.3%.